Pursuing the university's internationalization agenda - Joseph, Corina (UiTM Sarawak, 2021)
Oflate, Associate Professor Dr Corina Joseph has received several invitations from various organizations and universities in Indonesia to undertake different academic discourses. Firstly, Corina has been appointed as the Advisory Committee Member of the Sustainability Reporting Asia Global Certification Program under the Social Responsibility Asia in collaboration with Atma Jaya Catholic University.